Practical JBoss Seam projects - Farley, Jim. (Berkeley, Calif : Apress ; New York, NY : Distributed to the Book trade worldwide by Springer-Verlag New York, 2007)
Provides information on developing and running Web applications with JBoss Seam.
Introducing Seam -- Seam configuration and administration -- Component fundamentals -- Contexts and conversations -- Structured pageflow -- Security -- Business process management -- Rich web clients.
Includes index.
User level: Intermediate-Advanced.
Keywords: JBoss; JBoss (Computer software); Java (Computer program language); Web servers -- Management; Application software -- Development; Client/server computing; Web servers -- Management; Java (Computer language)